Auditoría de Gestión a la Asociación Agroartesanal de Productores Ecológicos de Palanda y Chinchipe, periodo 2021 - Zumba Capa, Valeria Verennice (2024)
The present Work of Curricular Integration entitled, AUDIT OF MANAGEMENT TO THE AGROARTISANAL ASSOCIATION OF ECOLOGICAL PRODUCERS OF PALANDA AND CHINCHIPE, PERIOD 2021, was developed in order to evaluate the internal control system, examining the levels of efficiency, efficacy and economy that the resources available in the partnership are managed, measuring in this way the objectives set. To comply with the Management Audit, a previous visit was made to the facilities of the association, collecting information and documentation necessary for the development of the audit, applying also research methods and techniques such as scientific, deductive, inductive, descriptive, analytical, synthetic and mathematical methods as well as techniques such as observation and bibliographic tools, the same ones were used to carry out the Phase I of Preliminary Knowledge and Phase II of Planning, with the visit and information gathered, the planning memorandum and the audit risk matrix were developed. In Phase III of Implementation, it was developed the audit program and questionnaire, determining the evaluation of the Internal Control to know the level of confidence and risk in the activities and operations that are carried out, obtaining as product significant findings, which were detailed in the narrative sheets with the respective evidence. The most representative activities of the Annual Operational Plan were verified to see if the provisions of the Annual Operational Plan are complied with. In addition, efficiency indicators were applied, such as evaluations for staff working in the association, training for all staff, level of professionalization, performance of activities, and indicators of effectiveness in the knowledge of the mission, vision, objectives, internal regulations; whereas in the economic indicators the acid test, inventory rotation, current liquidity and indebtedness were applied; after having carried out the respective management audit in the association, Phase IV Communication of Results is given, where a final report will be issued, which contains suggestions to improve the administration of APECAP; and finally in phase V of Follow-up a timetable is established for the fulfillment of the recommendations.